Veterinary treatment of fox casualties. Issue 3 (3rd March 2016) - Couper, David; Bexton, Steve
Abstract : Red foxes ( Vulpes vulpes ) are found throughout most of the northern hemisphere, and as an introduced species in Australia. In the UK, they are almost ubiquitous, although they are absent from many of the Scottish islands, the Scilly Isles and the Channel Islands. Their opportunistic lifestyle has enabled them to establish a large urban population in the UK and elsewhere in Europe, with the result that they are relatively common wildlife casualties. Reasons for presentation to veterinary surgeries include (allegedly) orphaned and abandoned cubs, trauma and sarcoptic mange. While foxes can generally be treated like domestic dogs medically and surgically, various aspects of vulpine behaviour must be taken into account for successful rehabilitation. This article describes how to handle and treat foxes that are presented in practice.